(untitled) (Physical Education, Health and Social Sciences, 2025)
The paper investigates the often-ignored but crucial role of women in countering violent extremism (CVE) in terms of their dual agency in promoting and countering extremist ideologies and violence. Traditionally, counterterrorism policy has been male-dominated and heavily security-focused, but some recent evidence shows that women can strategically develop community-based opportunities for the early detection of radicalization and dissemination of counter-narratives. Their contributions to countering violent extremism become invisible as a result of gender-blind contexts, limited representation, and failure to analyze intersections. By analyzing the current literature and accompanying case studies, it becomes evident that there are pressing gaps in research and policy, including data gathering, program design, and long-term impact assessment. The study recommends the incorporation of gender into CVE programs, additional support for women-led efforts, and the inclusion of women in decision-making and policy roles. By engaging women meaningfully in CVE, effectiveness will be increased and aid in fostering an inclusive and sustainable practice of peacebuilding